GERAKAN MASYARAKAT PEDULI LINGKUNGAN UNTUK MENINGKATKAN KESADARAN KEBERSIHAN DI SIDOARJO - Aulia Ayunita Wardatul Arifin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This activity aims to analyze the performance of the Environmental Care Community Movement (ECCM) in increasing sanitation awareness in the Sidoarjo community through the core methodology of participatory action. The main issues addressed are the high level of trash accumulation and the growth of weeds (water hyacinth) in Afvoer Kemambang, a vital water channel. The Environmental Care Community Movement (ECCM) was designed as a participatory action cycle intervention involving multi-sector collaboration between students, supervising lecturers, the local community, and formal institutions such as the Environmental Agency (EA). The implementation of concrete actions focused on the physical cleanup of the river area and the cleaning and maintenance of the campus garden, which is the action stage in the participatory action cycle. Methodologically, this approach prioritizes the utilization of the community's internal resources, such as students as trained resources and the logistical support of campus facilities, ensuring that the activities are driven and controlled independently. The results of the service activity show that the Environmental Care Community Movement (ECCM) successfully created a strong tripartite synergy, evidenced by active participation from the Environmental Agency (EA) and security institutions in the field, providing institutional support reinforcement for the action. The increase in sanitation awareness is proven to occur through experience, which is a direct result of the observation and reflection phases within the participatory action. This experience transforms cognitive understanding into behavioral commitment, increasing the sense of ownership and collective responsibility towards environmental cleanliness. The implementation of participatory action successfully became a model for sustainable empowerment, transforming an environmental issue into an asset-based collective action with the potential for replication.